Topical Issues of Preventing and Suppressing Crimes of Corruption in the Housing Sector - BURMISTROV, Igor A.; NIKODIMOV, Igor Yu.; ZAKHARTSEV, Sergey I.; MIRONOVA, Elena A.; ALIEVA, Gunel A. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
Analysis of the current situation in the fight against crime in Russia, in our opinion, shows that it is necessary to strengthen the role of the state in this process, and, consequently, improve the quality, efficiency, process of crime investigation, which includes not only the recognition of signs of offenses, collecting evidence, but also the ability to identify a system of factors and circumstances that contributed to the commission of a particular crime – with the aim of their subsequent elimination by methods other than the procedural, but otherwise legal. In this aspect, the authors, in the framework of this article, touch upon issues related to corruption offenses in the housing and utilities sector. The article considers the current state of affairs in the housing and utilities sector of Russia. It is argued that corruption in the housing and utilities sector is a kind of indicator of society that characterizes its socio-economic level and the viability of government. The corruption component in the activities of housing and public utilities in the formation of tariffs was considered. Offered options to combat this negative phenomenon.